Airtel : pricing in the cannibalisation era and transition to data - Sahay, Arvind; Tiwari, Tara (London : Indian Institute of Management, Ahmedabad, 2018)
Airtel, a telecommunications company, experienced increased competition after the entrance of Reliance Jio in 2017. Reliance Jio offered free calls for life and competitive tariff plans to consumers and as a result Airtel saw a decline in its average revenue per user. Airtel must create a new pricing plan to protect its revenue and market share of the Indian Telecommunications industry.
Originally Published InSahay, A., & Tiwari, T. (2018). Airtel: Pricing in the Cannibalisation Era and Transition to Data. IIMA/MAR0496. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Airtel (Firm); Competition -- India -- Case studies; Strategic planning -- Case studies; Telecommunication -- India -- Management -- Case studies